"I didn't mean to suggest anything like that!": Deniability and context reconstruction. (5th October 2021) - Mazzarella, Diana
Abstract : Verbal communication leaves room for interpretative disputes. Speakers can argue about what they mean by their words and negotiate their commitments in conversation. This article examines the deniability of implicitly communicated contents and addresses the question of what makes an act of denial seem more or less plausible to the addressee. I argue that denials bring about a process of reconstruction of the context of interpretation of the speaker's utterance and I illustrate how considerations of cognitive utility are the key determinant for distinguishing plausible from merely possible deniability.